2021
DOI: 10.2196/19820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Patient Portal Use on Patient Satisfaction: Survey and Partial Least Squares Analysis

Abstract: Background With digital delivery of health care services gaining prominence, patient portals have become a mainstay of many health care organizations. Despite the importance of patient portals, inconclusive data exist regarding the effect of patient portal use on patient satisfaction. Objective The aim of this study is to understand the relationship between the postadoptive use of patient portals and patient satisfaction outcomes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…Of note, both the technology and training interventions showed positive effects on patient satisfaction, consistent with prior evidence linking satisfaction to portal use, 3,39,40 tablet availability, 41 and perceptions about portals' usefulness. 42 For instance, patients receiving the in-person training may have learned to use functions that informed them about their health status and care plan, 31,32 which enabled them to ask more targeted questions, and this could have increased…”
Section: Effect Of Touch Intervention Among Patients Receiving Full-t...supporting
confidence: 79%
“…Of note, both the technology and training interventions showed positive effects on patient satisfaction, consistent with prior evidence linking satisfaction to portal use, 3,39,40 tablet availability, 41 and perceptions about portals' usefulness. 42 For instance, patients receiving the in-person training may have learned to use functions that informed them about their health status and care plan, 31,32 which enabled them to ask more targeted questions, and this could have increased…”
Section: Effect Of Touch Intervention Among Patients Receiving Full-t...supporting
confidence: 79%
“…Establishing and providing access to patients’ EHRs is an integral part of people-centered health systems in the World Health Organization’s global strategy for digital health [ 10 ]. In a recent study, Kinney and Sankaranarayanan [ 11 ] suggested that the use of patient portals may improve patients’ perceptions of their health care and the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic patient portals are secure websites or web-based applications that give patients access to their electronic medical records and allow for secure messaging between patients and providers. Patient portals have been associated with greater patient satisfaction and engagement in care [1][2][3] and fewer no-show appointments [4].…”
Section: Introductionmentioning
confidence: 99%